Indolo‐pyrido‐isoquinolin based alkaloid inhibits growth, invasion and migration of breast cancer cells via activation of p53‐miR34a axis - Dimiter B. Avtanski; Arumugam Nagalingam; Joseph E. Tomaszewski; Prabhakar Risbood; Michael J. Difillippantonio; Neeraj K. Saxena; Sanjay V. Malhotra; Dipali Sharma (Molecular Oncology, 2016)
The tumor suppressor p53 plays a critical role in suppressing cancer growth and progression and is an attractive target for the development of new targeted therapies. We synthesized several indolo‐pyrido‐isoquinolin based alkaloids to activate p53 function and examined their therapeutic efficacy using NCI‐60 screening. Here, we provide molecular evidence that one of these compounds, 11‐methoxy‐2,3,4,13‐tetrahydro‐1H‐indolo[2′,3′:3,4]pyrido[1,2‐b]isoquinolin‐6‐ylium‐bromide (termed P18 or NSC‐768219) inhibits growth and clonogenic potential of cancer cells. P18 treatment results in downregulation of mesenchymal markers and concurrent upregulation of epithelial markers as well as inhibition of migration and invasion. Experimental epithelial–mesenchymal‐transition (EMT) induced by exposure to TGFβ/TNFα is also completely reversed by P18. Importantly, P18 also inhibits mammosphere‐formation along with a reduction in the expression of stemness factors, Oct4, Nanog and Sox2. We show that P18 induces expression, phosphorylation and accumulation of p53 in cancer cells. P18‐mediated induction of p53 leads to increased nuclear localization and elevated expression of p53 target genes. Using isogenic cancer cells differing only in p53 status, we show that p53 plays an important role in P18‐mediated alteration of mesenchymal and epithelial genes, inhibition of migration and invasion of cancer cells. Furthermore, P18 increases miR‐34a expression in p53‐dependent manner and miR‐34a is integral for P18‐mediated inhibition of growth, invasion and mammosphere‐formation. miR‐34a mimics potentiate P18 efficacy while miR‐34a antagomirs antagonize P18. Collectively, these data provide evidence that P18 may represent a promising therapeutic strategy for the inhibition of growth and progression of breast cancer and p53‐miR‐34a axis is important for P18 function.